All-inorganic perovskite quantum dot light-emitting memories - Meng-Cheng Yen; Chia-Jung Lee; Kang-Hsiang Liu; Yi Peng; Junfu Leng; Tzu-Hsuan Chang; Chun-Chieh Chang; Kaoru Tamada; Ya-Ju Lee (Nature Communications, 2021)
Electric field induced ion migration is a well-known phenomenon in perovskite, but the consequences are notorious, and thus needs to be prevented. Here, on the other hand, the authors cleverly manipulate this event for realising resistive random-access memory and light-emitting electrochemical cell in one device based on CsPbBr3 quantum dots.